Secondary Somatic Embryogenesis in Centaurium erythraea Rafn - Milica D. Bogdanović; Katarina B. Ćuković; Angelina R. Subotić; Milan B. Dragićević; Ana D. Simonović; Biljana K. Filipović; Slađana I. Todorović (Plants, 2021)
Somatic embryogenesis (SE) is a developmental process during which plant somatic cells, under suitable conditions, produce embryogenic cells that develop into somatic embryos (se). SE is the most important method for plant propagation in vitro, having both fundamental and applicative significance. SE can be induced from different tissues and organs, but when se are used as explants, the process is recognized as secondary or cyclic SE. We induced secondary SE in Centaurium erythraea by application of 2,4-dichlorophenoxyacetic acid (2,4-D) and N-(2-chloro-4-pyridyl)-N′-phenylurea (CPPU). A medium containing 0.1 mgL−1 2,4-D and 0.25 mgL−1 CPPU was optimal in terms of the number of primary SE explants forming se, the number of well-developed se per explant, and morphological appearance of the obtained se. These concentrations allowed SE to progress through three cycles, whereas at higher concentrations of 0.2 mgL−1 2,4-D and 0.5 mgL−1 CPPU, only two cycles were achieved. Histological analysis revealed that secondary se are formed both directly and indirectly. Secondary SE readily germinated and converted into plantlets. Induction of cyclic SE contributes to the conservation efforts of this endangered medicinal plant and expands the spectrum of in vitro developmental pathways described in centaury—an emerging model in developmental biology.